PERANCANGAN MODEL PENDUKUNG KEPUTUSAN UNTUK PENENTUAN LOKASI INDUSTRI BERDASARKAN PROSES HIERARKI ANALITIK - Kusumaningrum, Retno (MATEMATIKA, 2006)
The Analytic Hierarchy Process (AHP), a decision-making method based upon division of problem spaces into hierarchies. This paper looks at AHP as a tool used in determination of industrial location. Solution of AHP method finished with the iteration process of through at scheme ofÂ  Pascal computer program to assist the calculation process. From result of program device which have been made to be obtained the highest total priority value (TPV) was potential distribution and promotion track